Feasibility of Anaerobic Co-Digestion of Waste Activated Sludge and Corn Straw to Produce Methane-Batch Experiment - Ji, Min; Jiang, Xiaogang; Wang, Fen (Asian Journal of Chemistry, 2013)
This work comprises, the feasibility of anaerobic co-digestion of waste activated sludge and corn straw to produce methane. It showed that co-digestion of waste activated sludge and corn straw could increase C/N of substrate and it was benefit for anaerobic digestion. Anaerobic co-digestion efficiency was higher than anaerobic digestion efficiency of pure waste activated sludge. It was found that co-digestion of waste activated sludge and corn straw could raise biogas yield and initial biogas production time was 3-6 days before initial time of pure waste activated sludge. Biogas production of co-digestion lasted for 27 days and cumulative yield was 7 times of anaerobic digestion of pure waste activated sludge.